Compare between of extracted and commercial vitamin B12 on biochemical parameters in experimental animals (Eurasian Medical Research Periodical, 2022)
The objective of this study is to provide an on the effectiveness of vitamin B12 for the treatment of anemia extracted from bacteria Lactobacillus rhamnosus after testing its ability to produce the vitamin, purifying it in the laboratory and determining the optimal condition for its and compared with commercial vitamin B12 that treatment of anemia . The results shown The results shown in show a significant decrease (P˂0.05) in cholesterol in groups G2,G3,G4,G5 than the control group G1 was ( 70.35, 91, 99.55,82.7) mg/dl consecutively compared with the control its 117.3 200mg/dl and the triglycerides decreased significantly (P˂0.05) in groups G2, G3, G4, and G5 than in the control group G1